The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.joms.2014.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Bisphosphonate Uptake in Areas of Tooth Extraction or Periapical Disease

Abstract: Purpose Bisphosphonates (BPs) are widely used for the management of bone diseases such as osteoporosis and bone malignancy. However, osteonecrosis of the jaws (ONJ) is a serious complication of BP treatment. ONJ lesions mainly occur after extraction of teeth deemed unrestorable or around teeth with active periodontal or periapical disease. Because socket healing or dental disease shows higher bone turnover, the authors hypothesized that preferentially high BP accumulation would be observed in these areas. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…Animal studies can complement clinical findings because they can be designed in a controlled environment, where experimental variables are more predictable and adjustable. Several animal models of ONJ have been reported that provide powerful tools in assessing disease pathophysiology . In the studies presented herein, we employed two mouse ONJ models in animals treated with high levels of ZA in the absence of tooth extractions, but in the presence of either experimental periapical disease or naturally occurring periradicular infection .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal studies can complement clinical findings because they can be designed in a controlled environment, where experimental variables are more predictable and adjustable. Several animal models of ONJ have been reported that provide powerful tools in assessing disease pathophysiology . In the studies presented herein, we employed two mouse ONJ models in animals treated with high levels of ZA in the absence of tooth extractions, but in the presence of either experimental periapical disease or naturally occurring periradicular infection .…”
Section: Discussionmentioning
confidence: 99%
“…Several animal models of ONJ have been reported that provide powerful tools in assessing disease pathophysiology. (30)(31)(32)(33)59,60) In the studies presented herein, we employed two mouse ONJ models in animals treated with high levels of ZA in the absence of tooth extractions, but in the presence of either experimental periapical disease or naturally occurring periradicular infection. (30)(31)(32) We have reported that these animals develop ONJ-like lesions with clinical bone exposure, and radiographic and histologic features such as periosteal bone formation, bone sclerosis, thickening of lamina dura, empty presence of osteocytic lacunae, and osteonecrosis resembling the human disease.…”
Section: Discussionmentioning
confidence: 99%
“…This is why increased uptake may predispose such sites to higher BP doses and increase susceptibility to BP effects. Although this may not demonstrate a general increase in bone turnover in the jaws, it does show a localized increase in potentially future ONJ sites [25]. The increased bone resorption in the setting of dental disease, coupled with the thin overlying mucosa and a direct pathway through the periodontal ligament with the external environment, make the jaws a suitable breeding ground for ONJ to develop.…”
Section: Proposed Hypotheses Of Mronj Pathophysiologymentioning
confidence: 99%
“…1820 BPs form strong bidentate or tridentate bonds with calcium phosphate mineral, and as a result concentrate in hydroxyapatite (HA), particularly at skeletal sites of active metabolism including sites of infection and inflammation. 21 BPs also exhibit exceptional stability against both chemical and biological degradation. 22 BP-fluoroquinolone antimicrobial activity is complex and is related to the specific strain of pathogen tested, the choice of antibiotic and covalently bound BP moiety, the tether length between the two constituents, the bone binding affinity of the BP, the adsorption–desorption equilibria of the BP, and the stability/lability and kinetics of the linkage moiety used for conjugation.…”
Section: Introductionmentioning
confidence: 99%